Uporaba serijsko izdelanih ortoz za gleženj pri osebah po preboleli možganski kapi - Lahovič, Tjaša (Rehabilitacija (Ljubljana), 2014)
Background: It is known that ankle and foot orthoses ways improve gait pattern in patients after stroke in many. Mass-produced orthoses for the ankle are available on the Slovenian market to patients with impaired upper motor neuron. The aim of our study was to assess the influence of such ankle orthoses on irregularities in gait, the pressure on the impaired foot and walking speed in patients after stroke with mild abnormalities in gait. Methods: Fourteen patients after stroke who were admitted to inpatient rehabilitation at the University Rehabilitation Institute in Ljubljana for the first time were included in the study. They were fitted with a mass-produced ankle orthosis and then clinical analysis of their gait pattern was conducted, and the 10-meter walking test and the timed-up-and-go test were performed. Plantar pressures were measured using the F-Scan system with and without the orthosis. Results: Clinical gait analysis showed that the ankle orthosis partially prevented foot drop in the swing phase. The F-Scan measurements did not show any significant differences in the distribution of pressure when comparing the patients' walking with and without the ankle orthosis. The timed tests showed significant improvement when using the orthosis: the mean time of the 10-meter walking test with an ankle orthosis was 15.6 seconds and without orthosis it was 17.3 seconds (p<0.01); with ankle orthosis the patients completed the timed-up-and-go test in 17.3 seconds on average whereas without orthosis the mean time was 18.2 seconds (p <0.05). Conclusion: Mass-produced orthoses for the ankle partially improve gait in patients after stroke and with mild paresis of the lower limb leading to moderate abnormalities in gait pattern.
Keywords: Ankle; foot drop; gleženj; hitrost hoje; možganska kap; Orthotic Devices; ortotski pripomočki; padajoče stopalo; Stroke; walking speed